Automatic piano performance interaction system based on greedy algorithm for dexterous manipulator - Yufei Wang; Junfeng Yao; Yalan Zhou; Zefeng Wang (Virtual Reality & Intelligent Hardware, 2024)
With continuous advancements in artificial intelligence (AI), automatic piano-playing robots have become subjects of cross-disciplinary interest. However, in most studies, these robots served merely as objects of observation with limited user engagement or interaction. To address this issue, we propose a user-friendly and innovative interaction system based on the principles of greedy algorithms. This system features three modules: score management, performance control, and keyboard interactions. Upon importing a custom score or playing a note via an external device, the system performs on a virtual piano in line with user inputs. This system has been successfully integrated into our dexterous manipulator-based piano-playing device, which significantly enhances user interactions.